2018
DOI: 10.4317/jced.54871
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction in complete denture wearers with and without adhesives: A randomized, crossover, double-blind clinical trial

Abstract: BackgroundThe purpose of this study was to compare the satisfaction of patients regarding retention, stability and accumulation of particles with a randomized, double-blind crossed method in users with complete dentures with and without adhesive.Material and MethodsSeventeen edentulous individuals were randomized and received new upper and lower complete dentures. After a period of adaptation, they participated in some masticatory tests and clinical revisions, after use the protheses with and without the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 36 publications
1
21
0
1
Order By: Relevance
“…This result differs from that reported in previous studies. Torres-Sánchez et al (2018) carried out a crossover doubleblind comparison of groups using 2 types of denture adhesives and no adhesive, and in the subjective evaluations, they found that the level of patient satisfaction was greater in the groups using denture adhesives. Marin et al (2014) used subjective evaluations in a crossover RCT with new dentures and reported improved comfort of wearing mandibular dentures, retention of mandibular dentures, general satisfaction, and chewing as a result of denture adhesive use.…”
Section: Discussionmentioning
confidence: 99%
“…This result differs from that reported in previous studies. Torres-Sánchez et al (2018) carried out a crossover doubleblind comparison of groups using 2 types of denture adhesives and no adhesive, and in the subjective evaluations, they found that the level of patient satisfaction was greater in the groups using denture adhesives. Marin et al (2014) used subjective evaluations in a crossover RCT with new dentures and reported improved comfort of wearing mandibular dentures, retention of mandibular dentures, general satisfaction, and chewing as a result of denture adhesive use.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1133 patients with an average age of 67 years were included in the studies, they were individuals in which the total dentures already had a time of use or who accepted the manufacture of new dental prostheses. Most studies were conducted in universities (Kelsey et al, 1997;Uysal et al, 1998;Kulak et al, 2005;Pradíes et al, 2009;Koronis et al, 2012;Munoz et al, 2012;Bartlett et al, 2013;Marin et al, 2014;Guimarães et al, 2018;Torres-Sánchez et al, 2018;Ohwada et al, 2020) and only one in a private practice (Psillakis et al, 2004). Most studies included patients of both sexes (Kelsey et al, 1997;Uysal et al, 1998;Kulak et al, 2005;Pradíes et al, 2009;Munoz et al, 2012;Koronis et al, 2012;Bartlett et al, 2013;Ohwada et al, 2020).…”
Section: General Data From Included Studiesmentioning
confidence: 99%
“…Most studies included patients of both sexes (Kelsey et al, 1997;Uysal et al, 1998;Kulak et al, 2005;Pradíes et al, 2009;Munoz et al, 2012;Koronis et al, 2012;Bartlett et al, 2013;Ohwada et al, 2020). Eight studies randomly divided individuals into groups to compare different brands of adhesive and all selected studies assessed patient satisfaction using questionnaires and scales (Kelsey et al, 1997;Uysal et al, 1998;Psillakis et al, 2004;Kulak et al, 2005;Pradíes et al, 2009;Koronis et al, 2012;Munoz et al, 2012;Bartlett et al, 2013;Marin et al, 2014;Guimarães et al, 2018;Torres-Sánchez et al, 2018;Nishi et al, 2020;Ohwada et al, 2020). Most studies included patients who had less than 7 years of total prosthesis use (Kelsey et al, 1997;Uysal et al, 1998;Psillakis et al, 2004;Kulak et al, 2005;Pradíes et al, 2009;Mañes et al, 2011;Munoz et al, 2012;Bartlett et al, 2013;Guimarães et al, 2018;Torres-Sánchez et al, 2018;Ohwada et al, 2020) and five studies made new prostheses (Koronis et al, 2012;Marin et al, 2014;AlRumaih et al, 2017;Nishi et al, 2020;Ohwada et al, 2020).…”
Section: General Data From Included Studiesmentioning
confidence: 99%
“…Many patients with dentures use denture adhesives daily because they provide retention and stability, improving both function and comfort 1‐3 . Moreover, the product is easily available at any pharmacy, with no need for a prescription and at an affordable price 4 .…”
mentioning
confidence: 99%
“…Many patients with dentures use denture adhesives daily because they provide retention and stability, improving both function and comfort. [1][2][3] Moreover, the product is easily available at any pharmacy, with no need for a prescription and at an affordable price. 4 However, the effects that this type of product can have on oral mucosa cells have not been extensively tested, despite the fact that the substance is in contact with the oral mucosa many hours a day, or could even be ingested by the user.…”
mentioning
confidence: 99%